0112 Hils google glass. (2nd November 2015) - Gay, Christopher; Graby, Matthew; Charlton, Olivia; Riby, Stuart
Abstract : Background/context: The HILS Technical Team obtained Google Glass as the 'explorer' phase of the product ended. Whilst its use domestically has proved controversial 1it has found a firm footing in healthcare with applications ranging from providing live patient data to sharing the headsets point of view to a larger training audience 2 Description of innovation or topic: HILS have a variety of ideas to put Google Glass to use in improving training. Using the headset to provide a range of new point of views in simulated scenarios, such as - The patient's perspective - The delegates perspective Recording 'hands on' 'how to' videos of technical procedures and making them available for training Streaming live procedures (real or otherwise) to a geographically distanced audience All of these methods have their challenges and will be documented to share the experiences. Improvements/outcomes (anticipated or recorded): We believe that bringing in a closer perspective will deepen empathy in scenarios involving behavioural and human factors. We believe that any technical videos will be enhanced and better understood with the more personal perspective. We believe that using the live streaming function will widen participation in training Take home messages: Domestic technology can find unexpected uses in healthcare A different perspective can enhance training References: http://www.businessinsider.com/nobody-really-likes-google-glass-2013-5?IR=T http://www.telegraph.co.uk/health/healthnews/10851116/First-operation-streamed-live-with-surgeon-wearing-Google-glass.html)